Análisis numérico de los gradientes térmicos por cargas de temperatura en puentes de concreto reforzado (2022)
The environmental thermal changes produce deformations and stresses in the structures that can accelerate the cracking in the concrete and, consequently, shorten its durability. Currently, Colombia lacks specific studies on thermal loads on bridges. Consequently, a numerical model is developed programming in Python an algorithm that solves the one-dimensional problem in transient state to simulate heat transfer mechanism in the concrete deck of a concrete bridge. The results are validated with academic reference problems. In addition, a comparison is made with surface temperature data with thermal camera monitoring measurements for two bridges located in Bogotá and Neiva. The numerical model gives similar results to the reference problems and conservative results with reference to the monitoring data.